2010
DOI: 10.1007/s11046-010-9347-9
|View full text |Cite
|
Sign up to set email alerts
|

Infection Risk by Dermatophytes During Storage and After Domestic Laundry and Their Temperature-Dependent Inactivation

Abstract: In the developed countries infections of the feet (tinea pedis, athlete's foot) and nails (onychomycosis) with the anthropophile fungus Trichophyton rubrum are most common. We examined the propagation of dermatophytes before and during domestic laundering. About 10% of the infectious material was transferred from contaminated textiles to sterile textiles during storage in a clothes basket simulation indicating a high infection risk during storage. This was evaluated with two quantification techniques: cultivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 27 publications
1
57
0
1
Order By: Relevance
“…When soiled clothing is laundered at home, it should be transported in a sealed plastic bag, kept separate from household laundry, emptied from the bag directly into a washing machine, and thoroughly machine dried after completion of the wash cycle. [162][163][164] 4. Spill Response and Decontamination Spills and splashes of potentially infective substances should be immediately contained with absorbent material (eg, paper towels, sawdust, or cat litter).…”
Section: Handling Of Laundrymentioning
confidence: 99%
“…When soiled clothing is laundered at home, it should be transported in a sealed plastic bag, kept separate from household laundry, emptied from the bag directly into a washing machine, and thoroughly machine dried after completion of the wash cycle. [162][163][164] 4. Spill Response and Decontamination Spills and splashes of potentially infective substances should be immediately contained with absorbent material (eg, paper towels, sawdust, or cat litter).…”
Section: Handling Of Laundrymentioning
confidence: 99%
“…It should be pointed out that mycological examination of the cloths at the time the case was reported was more likely to yield organisms transferred from the patient's lesion to the fabrics, rather than confirm the cloth as source of the infection-hence we saw no benefit in doing so. However, the possibility of transmission of ringworm through clothes has been reported before [18]. Acquisition of ringworm from second-hand clothes is of dire implications in this part of the world, since majority of Nigerians, even those at the upper socio-economic stratum of the society, have significant taste for second-hand wears.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial fabrics can be a part of primary and secondary prevention strategies for skin mycoses. Nevertheless, the antimicrobial effect cannot replace efficient washing processes, which should be conducted at temperatures ≥ 60 °C 14 . The variation of dermatophyte susceptibility, however, has to be kept in mind when the efficacy of such textiles is tested.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, shoes, towels and bed linen have to be considered as parts of the chain of infection. Recently, it could be shown that T. rubrum can be transferred from contaminated to non‐contaminated textiles during storage in the laundry basket and during low‐temperature domestic washing procedures 14 . This finding is especially important for persons suffering from tinea pedis, also known as athlete’s foot, where the causative pathogens can persist on the patients’ socks.…”
Section: Introductionmentioning
confidence: 99%